The Role of Death-Anxiety-Induced Fear of COVID-19 in Compliance With and Acceptance of Government-Issued COVID-19 Regulations - Kehr, Hugo M.; Bakaç, Cafer; Jais, Marius; Brunner, Dorothee; Voigt, Julian; Holzemer, Lea (Frontiers in Psychology, 2022)
The present research was conducted to empirically examine whether death anxiety is the fundamental fear that feeds people’s fear of COVID-19 and leads to increased behavioral compliance with and acceptance of COVID-19 regulations. Results from an online survey of 313 participants from New York City show that death anxiety was, indeed, positively associated with behavioral compliance with, but not acceptance of, COVID-19 regulations via an increased fear of COVID-19. Hence, media campaigns that are designed to increase people’s compliance with restrictive COVID-19 measures by stirring up their fear of death are likely to meet their target, but they do not necessarily lead to increased public acceptance of the measures taken.